The Experience of 2 Independent Schools With In‐Person Learning During the COVID‐19 Pandemic. (25th March 2021) - Gillespie, Darria L.; Meyers, Lauren A.; Lachmann, Michael; Redd, Stephen C.; Zenilman, Jonathan M.
ABSTRACT: BACKGROUND: In 2020, US schools closed due to SARS‐CoV‐2 but their role in transmission was unknown. In fall 2020, national guidance for reopening omitted testing or screening recommendations. We report the experience of 2 large independent K‐12 schools (School‐A and School‐B) that implemented an array of SARS‐CoV‐2 mitigation strategies that included periodic universal testing. METHODS: SARS‐CoV‐2 was identified through periodic universal PCR testing, self‐reporting of tests conducted outside school, and contact tracing. Schools implemented behavioral and structural mitigation measures, including mandatory masks, classroom disinfecting, and social distancing. RESULTS: Over the fall semester, School‐A identified 112 cases in 2320 students and staff; School‐B identified 25 cases (2.0%) in 1400 students and staff. Most cases were asymptomatic and none required hospitalization. Of 69 traceable introductions, 63 (91%) were not associated with school‐based transmission, 59 cases (54%) occurred in the 2 weeks post‐thanksgiving. In 6/7 clusters, clear noncompliance with mitigation protocols was found. The largest outbreak had 28 identified cases and was traced to an off‐campus party. There was no transmission from students to staff. CONCLUSIONS: Although school‐age children can contract and transmit SARS‐CoV‐2, rates of COVID‐19 infection related to in‐person education were significantly lower than those in the surrounding community. However, social activities among students outside of school undermined those measures and should be discouraged, perhaps with behavioral contracts, to ensure the safety of school communities. In addition, introduction risks were highest following extended school breaks. These risks may be mitigated with voluntary quarantines and surveillance testing prior to reopening.